Early burial mud diapirism and its impact on stratigraphic architecture in the Carboniferous of the Shannon Basin, County Clare, Ireland. Issue 1 (16th July 2018) - Blanchard, Sébastien; Matheson, Edward J.; Fielding, Christopher R.; Best, James L.; Bryk, Alexander B.; Howell, Kalin J.; Monson, Charles C.; Mahoney, Gosia; Peakall, Jeffrey
Abstract: Delta fronts are often characterized by high rates of sediment supply that result in unstable slopes and a wide variety of soft‐sediment deformation, including the formation of overpressured and mobile muds that may flow plastically during early burial, potentially forming mud diapirs. The coastal cliffs of County Clare, western Ireland, expose Pennsylvanian (Namurian) delta‐front deposits of the Shannon Basin at large scale and in three dimensions. These deposits include decametre‐scale, internally chaotic mudstone masses that clearly impact the surrounding sedimentary strata. Evidence indicates that these were true mud (unlithified sediment) diapirs that pierced overlying strata. This study documents a well‐exposed ca 20 m tall mud diapir and its impact on the surrounding mouth‐bar deposits of the Tullig Cyclothem. A synsedimentary fault and associated rollover dome, evident from stratal thicknesses and the dip of the beds, define one edge of the diapir. These features are interpreted as recording the reactive rise of the mud diapir in response to extensional faulting along its margin. Above the diapir, heterolithic sandstones and siltstones contain evidence for the creation of localized accommodation, suggesting synsedimentary filling, tilting and erosion of a shallow sag basin accommodated by the progressive collapse of the diapir. Two other diapirs are investigated using three‐dimensional models built from 'structure from motion' drone imagery. Both diapirs are interpreted to have grown predominantly through passive rise (downbuilding). Stratal relationships for all three diapirs indicate that they were uncompacted and fluid‐rich mud beds that became mobilized through soft‐sediment deformation during early burial (i.e. <50 m, likely <10 m depth). Each diapir locally controlled the stratigraphic architecture in the shallow subsurface and potentially influenced local palaeocurrents on the delta. The mud diapirs studied herein are distinct from deeper 'shale diapirs' that have been inferred from seismic sections worldwide, now largely disputed.